PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH PADA BKK PASAR KLIWON SURAKARTA DENGAN KEPUASAN NASABAH SEBAGAI VARIABEL INTERVENING - Endang Saryanti; Budhi Poniman; Shandy Marsono (STIE AUB Surakarta, 2016)
This study aims to determine the Effects of tangible, reliability, responsiveness, assurance and empathy on customer loyalty at BKK Pasar Kliwon Surakarta with satisfaction as an intervening variable. This study is a survey research. The data used primary data collected through questionnaires to customers BKK Pasar Kliwon Surakarta. The data obtained were tested using the test validity, reliability, linearity test, path analysis, t test, F test, test R2 in total. The results of the t test, the first equation shows that the variables of the tangible has significant effect on customer satisfactions. Reliability has significan effect on customer satisfaction. Responsiveness has significan effect on customer satisfaction. Assurance has significan effect on customer satisfaction. Empathy has significan effect on customer satisfaction. Tangible has significant effect on loyalty. Reliability has significant effect on loyalty. Responsiveness has significant effect on loyalty. Assurance has significant effect on loyalty. Empathy has significant effect on loyalty. Customer satisfactions has significant effect on loyalty. Total R2 value was 86,8%. This means that loyalty, simultaneously test result (Test F) can be inferred that tangible, reliability, responsiveness, assurance, empathy and customer satisfaction has significantly influence loyalty at BKK Pasar Kliwon Surakarta. The results of path analysis, the use of intervening variables, in this path analysis showed that the variables of tangible most effective variable to increase loyalty as a positive and significant impact on loyalty. Keywords : tangible, reliability, responsiveness, assurance and empathy , customer loyalty and satisfaction